An 8-week 24-form Tai Chi intervention on cognition in Chinese college students overusing short videos: a randomized controlled trial - Li, Yu-fan; Xiao, Chong-yao; Cai, Rong-xin (Frontiers in Psychology, 2025)
IntroductionThis study evaluated the effect of an 8-week practice of 24 forms of Tai Chi on cognition in college students aged 18–21 years who were overexposed to short videos.MethodsA total of 1803 short video usage questionnaires were distributed at a college in Fujian Province, China, and 1790 valid questionnaires were collected. Sixty college students who scored in the top 20% on the questionnaire were randomly assigned to a Tai Chi experimental group (TCG) or an overuse control group (OCG), with 30 participants in each. The 32 students with the lowest 20% questionnaire scores were selected as the low-frequency-use control group (LCG). The TCG participated in 24-form Tai Chi training three times a week for 8 weeks. The OCG and LCG maintained their original habits without intervention. All groups were tested before, at the end of, and 2 months after training, using the digit string memory test, word delineation test, and three E-prime tests, which test memory, sustained attention, selective attention, and comprehensive attention.ResultThere were no significant differences in the digital string memory test, the number cancellation test, and oddball paradigm results. In the Go/No-go experiment, accuracy showed no significant difference across groups before and after the intervention. Reaction times for TCG and OCG were significantly higher than LCG pre-intervention (p < 0.05). Post-intervention, TCG reaction times significantly decreased (p < 0.05), aligning with LCG and differing significantly from OCG. Two months post-experiment, reaction times were similar across all groups. In the Stroop test, no significant accuracy differences were found before and after the intervention. Pre-intervention, TCG and OCG reaction times were significantly longer than LCG (p < 0.05). Post-intervention, reaction times decreased for TCG and OCG, with TCG’s decline being more significant, aligning with LCG (p < 0.05). Two months post-experiment, reaction times became similar across all groups with no significant differences.DiscussionOveruse of short videos correlates with declines in sustained and comprehensive attention in college students. Tai Chi positively impacted sustained and comprehensive attention in students overusing short videos but had no significant effect on memory and selective attention. When Tai Chi training is discontinued, its positive effects gradually dissipate.